Rosacea – a modern view of diagnostics and treatment - Gawęda, Agnieszka; Babiak, Rafał; Bajak, Karolina; Czuchryta, Paulina; Domańska, Anastazja; Grabek, Agata; Rutkowska, Julia; Rzęsa-Tokarczyk, Żaneta; Skorek, Klaudia; Urbańczyk, Agnieszka (Journal of Education, Health and Sport, 2023)
Introduction: Rosacea is a chronic inflammatory skin disease affecting central region of the face. Main symptoms consist of erythema, flushing, telangiectasia, phymatous changes and inflammatory papules and pustules. It can also affect eyes, causing blepharitis, conjunctivitis, keratitis or lid margin telangiectasia. Rosacea can negatively affect the quality of life, causing low self-esteem, avoidance of social interactions and mental health issues such as anxiety and depression. There are two classifications of rosacea, one from 2002 focusing on subtypes, and new phenotype-based classification. Phenotype-based approach allows individual management of each patient instead of categorizing by predefined subtype. Due to increased frequency of Demodex infestation in patients with rosacea, diagnosis and treatment of demodicosis can be helpful in management of rosacea. General treatment of rosacea consists of combination of oral and topical therapies, choosing adequate skincare cosmetics, laser therapies and avoidance of identified trigger factors specific for the patient. The aim of the study: This study aims to gather current knowledge about classification, diagnostics, skincare and treatment of rosacea. Materials and methods: This review was based on available data collected in the PubMed database, using the keywords: ‘rosacea’, ‘ocular rosacea’, ‘rosacea treatment’. Conclusions: The treatment of rosacea requires selection of appropriate treatment depending on symptoms specific for the patient. Because of increased Demodex infestation present in some of the patients with rosacea, eradication can mitigate rosacea symptoms. Identification and avoidance of trigger factors and assortment of adequate skincare products are also substantial parts of management of rosacea and can alleviate rosacea symptoms.